Development of a Multiplex PCR Assay for Detection of Pseudomonas fluorescens with Biofilm Formation Ability. Issue 10 (26th September 2017) - Xu, Yu; Chen, Wanyi; You, Chunping; Liu, Zhenmin
Abstract : Abstract: Under the cold storage and processing conditions of raw milk, the psychrotrophic Pseudomonas fluorescens is usually found as predominant bacteria causing its spoilage. In this study, a multiplex PCR assay was developed for rapid and selective detection of P. fluorescens with biofilm formation ability. The target sequences were 2 genes ( adnA and fliC ) related to biofilm formation and flagella biosynthesis of P. fluorescens . The specificity of the mPCR assay was evaluated with 7 reference strains, isolated from raw milk, belonging to P. fluorescens, Pseudomonas fragi, Pseudomonas lundensis, Pseudomonas putida, Pseudomonas monteilii, and 2 unclassified Pseudomonas species ( Pseudomonas sp1 and Pseudomonas sp8). The detection limit for the target strain was 10 2 CFU/mL. Seventy‐three strains were evaluated by the mPCR assay. The adnA gene was detected in 23 strains while fliC gene was detected in only 3 strains. However, both target genes ( adnA and fliC ) were detected by amplification in 12 strains belonging to P. fluorescens species. The biofilm formation ability of P. fluorescens following cultivation in 10% UHT milk at 30 °C or 4 °C were evaluated by the microtiter plate assay. The result showed that all the P. fluorescens strains with the target gene ( adnA or fliC, or both 2 genes) had the biofilm‐forming ability. The phylogenetic analysis showed that adnA gene tree had a higher resolution than rpoB tree, and the strains in adnA phylogenetic dendrogram could be divided into 4 different groups according with the matrix of their biofilm‐forming ability. The results indicated a promising use of adnA gene as a taxonomic marker for subdividing P. fluorescens . Practical Application: A mPCR assay targeting adnA and fliC genes showed rapid and reliable detection of P. fluorescens with biofilm formation ability, which could be useful to detect this contamination in milk samples.